2020
DOI: 10.5588/ijtld.20.0082
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline and delamanid result in low rates of unfavourable outcomes among TB patients in Eswatini

Abstract: SETTING: Since 2015, Eswatini has been scaling up bedaquiline (BDQ) and delamanid (DLM) based drug-resistant TB treatment regimens under programmatic conditions.OBJECTIVE: Identification of factors associated with treatment outcomes in patients receiving BDQ and/or DLM either as a new treatment initiation or drug substitution.DESIGN: This is a retrospective cohort study of patients receiving BDQ and/or DLM in Eswatini between March 2015 and October 2018. We describe factors associated with unfavourable treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…These findings are in line with other bedaquiline deployment experiences from high HIV and tuberculosis burden areas [27][28][29], which reported that the early use of BDQ resulted in decreases in MDR/RR-TB-related mortality and treatment failure [6]. In addition, the included studies indicated that patients started on bedaquiline had better treatment outcomes [7,9,10,14,23].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are in line with other bedaquiline deployment experiences from high HIV and tuberculosis burden areas [27][28][29], which reported that the early use of BDQ resulted in decreases in MDR/RR-TB-related mortality and treatment failure [6]. In addition, the included studies indicated that patients started on bedaquiline had better treatment outcomes [7,9,10,14,23].…”
Section: Discussionsupporting
confidence: 83%
“…Since the introduction of bedaquiline, limited studies in Africa have reported on the use, benefits, and challenges of this drug [25,26]. Hence, the current study aimed to conduct a situational analysis of the introduction and use of the novel drug BDQ in shorter regimens for the treatment of MDR-TB and XDR in patients with TB [8][9][10][11][12][13]21]. To our knowledge, this review contributes to the evaluation and analysis of bedaquiline introduction and usage by healthcare practitioners in Africa, as well as its successes and challenges in the treatment of MDR-TB and XDR-TB patients on the continent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical increase of side effects (especially QT prolongation), has been of concern about this combination. However, some reports suggest that this problem could have been overestimated, and the combination could be administered safely and with good efficacy [48][49][50].…”
Section: Clinical Efficacymentioning
confidence: 99%
“…In a subsequent Phase 3 study a delamanid-containing regimen did not meet the pre-specified non-inferiority criteria with regard to the median time to SCC over 6 months compared to OBR alone; however, a significant shorter time to SCC was demonstrated in sensitivity analyses and in subgroup analyses in patients without cavitation and/or fluoroquinolone resistance [43] . While global experience with delamanid remains limited, some data support its effectiveness in a multidrug background regimen [21] , [44] , [45] , [46] . Ongoing clinical trials evaluate delamanid in various oral regimens of 6–12 months duration in rifampicin-resistant (RR), MDR and FQ-resistant TB, some also in combination with bedaquiline (endTB – Table 1 ) and will provide a better understanding of its role in current MDR TB management.…”
Section: Introductionmentioning
confidence: 99%